Overexpression of the C-domain of angiotensin-converting enzyme reduces melanoma growth by stimulating M1 macrophage polarization - Khan, Zakir (J Biol Chem, 2019)
Angiotensin-converting enzyme (ACE) can hydrolyze many peptides and plays a central role in controlling blood pressure. Moreover, ACE overexpression in monocytes and macrophages increases resistance of mice to tumor growth. ACE is composed of two independent catalytic domains. Here, to investigate the specific role of each domain in tumor resistance, we overexpressed either WT ACE (Tg-ACE mice) or ACE lacking N- or C-domain catalytic activity (Tg-NKO and Tg-CKO mice) in the myeloid cells of mice. Tg-ACE and Tg-NKO mice exhibited strongly suppressed growth of B16-F10 melanoma because of increased ACE expression in macrophages, whereas Tg-CKO mice resisted melanoma no better than WT animals. The effect of ACE overexpression reverted to that of the WT enzyme with an ACE inhibitor but not with an angiotensin II type 1 (AT1) receptor antagonist. ACE C-domain overexpression in macrophages drove them toward a pronounced M1 phenotype upon tumor stimulation, with increased activation of NF-κB and signal transducer and activator of transcription 1 (STAT1) and decreased STAT3 and STAT6 activation. Tumor necrosis factor α (TNFα) is important for M1 activation, and TNFα blockade reverted Tg-NKO macrophages to a WT phenotype. Increased ACE C-domain expression increased the levels of reactive oxygen species (ROS) and of the transcription factor C/EBPβ in macrophages, important stimuli for TNFα expression, and decreased expression of several M2 markers, including interleukin-4Rα. Natural ACE C-domain–specific substrates are not well-described, and we propose that the peptide(s) responsible for the striking ACE-mediated enhancement of myeloid function are substrates/products of the ACE C-domain.